International Migration in Europe New Trends and New Methods of Analysis - Simon, Patrick; Bonifazi, Corrado; Okólski, Marek; Schoorl, Jeannette (Amsterdam University Press, 2008)
Over the past twenty years international migration issues have gained a growing importance in public debate in most of the European countries. Public opinions are more and more concerned about the arrival of new immigrants and about the problems of integration processes. International Migration in Europe addresses some of the new aspects of European international migration. Different aspects are considered and different disciplinary perspectives are used in the fifteen chapters. In particular, attention has been devoted to analyse new forms of migration, the evolution of regional patterns, the intergenerational process of migrant integration and the use of special survey in migration studies.